The jungle book [videorecording (Blu-ray + DVD)] - Anderson, Ken, 1909-1993; Clemmons, Larry, 1906-1988; Wright, Ralph, 1908-1983; Gerry, Vance; Kipling, Rudyard, 1865-1936 (Disney, 2022)
Disney's swingin' classic is a song-filled celebration of friendship. Embark on a thrilling adventure-filled journey with Mowgli as he travels deep into the jungle and learns "The Bare Necessities" of life from happy-go-lucky Baloo the bear. Meet Bagheera, the wise panther, and jazzy King Louie, the orangutan. But watch out for the cunning tiger Shere Khan and Kaa, the ssssneakiest snake in the jungle!